Penggunaan Dyadic Essay Technique Dalam Pembelajaran Writing Mahasiswa Bahasa Inggris di STAIN Bengkalis - Mayasari, Wan Julia (Akademika : Jurnal Keagamaan dan Pendidikan, 2024)
Character building is a process of understanding the relationships experienced by every In learning English, there are four skills that relate to each other namely; listening, reading, writing and speaking. One of techniques in learning writing is using Dyadic Essay. The aim of the research : 1) to find out the English students’ ability before being conducted by using Dyadic Essay Technique, 2)  to find out the English students’ ability after being conducted by using Dyadic Essay Technique and 3) to find out the significant effect of using Dyadic Essay Technique. The total respondents were eighteen students of English Study Program. The findings showed : 1) the students’ writing ability before being conducted by using Dyadic Essay technique was 29.03, 2) the students’ writing ability after being conducted by using Dyadic Essay technique was 55.83, and 3) there is significant effect in using Dyadic Essay technique where ttest  is higher than ttable in significance level of 5% and 1% is 2.05 > 6.05 < 2.76. In sum, Dyadic Essay Technique was effective to improve the students’ ability in writing.